Capaian dan Proyeksi Kondisi Hukum Indonesia - Mahfud MD (Jurnal Hukum IUS QUIA IUSTUM, 2009)
To review the achievements of legal development during reformation era, shall be a parameter to be a foundation; which are some causes that led to the need for legal reform. In other word, it need to be identified what were the problems of legal development during the New Order era which in turns pushed to the rise of legal reform subsequently after political reform in 1998. There were problems addressed by legal reform, such as, the amendment of 1945 Indonesian Constitution, judicial reform through the amendment of Judicial Power Act, the inception of Corruption Eradication Commission, and also the inception of some new bodies which are considered to be helpful for the purpose of an effective legal enforcement and the maintenance of democracy.Keywords: : achievement, projection, current Indonesian legal system